A novel design technique for generating building form - KAYED, MAYS N. A. (2018)
This dissertation sets out to develop a novel design technique for generating building form in the early stage of the design. It recognizes generative design approaches potential to explore form integrally with instant evaluation process and questions the potential of enabling the generation of creativity aspects of the design process in such trajectory. The development of the technique is initiated by proposing an exploratory methodology where a procedural structure for the technique is formulated from four stages: “backward triangulation” stage, forward building formation stage, evaluation stage and selection stage. Each stage contains number of processes that replace the traditional design tasks. The development of the technique extended by developing mechanisms to maintain aspects related to design creativity by pure geometric abstraction of basic spatial relations. The theoretical framework of the technique was successfully tested out and validated by implementing it over serious of examples that are categorized into three groups: examples directed to test out the proposed variables in each process, examples directed to validate the ability of whole technique to generate forms for a hypothetical project requirements and examples of scripting the mechanisms using the algorithmic editor interface and the visual programming language Grasshopper incorporated with Rhinoceros 3D software."